2015
DOI: 10.1016/j.nima.2015.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Post-growth annealing of Bridgman-grown CdZnTe and CdMnTe crystals for room-temperature nuclear radiation detectors

Abstract: a b s t r a c tBridgman-grown cadmium zinc telluride (CdZnTe or CZT) and cadmium manganese telluride (CdMnTe or CMT) crystals often have Te inclusions that limit their performances as X-ray-and gamma-raydetectors. We present here the results of post-growth thermal annealing aimed at reducing and eliminating Te inclusions in them. In a 2D analysis, we observed that the sizes of the Te inclusions declined to 92% during a 60-h annealing of CZT at 510 1C under Cd vapor. Further, tellurium inclusions were eliminate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…Some of the smaller inclusions in the upper side of the image have been eliminated while other were replaced with much smaller inclusions. The change in shape, reduction in size, and elimination could be attributed to two major processes [14], viz. reaction between Te inclusions and Cd that diffused into the CdMnTe matrix, and diffusion of Te within the matrix.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the smaller inclusions in the upper side of the image have been eliminated while other were replaced with much smaller inclusions. The change in shape, reduction in size, and elimination could be attributed to two major processes [14], viz. reaction between Te inclusions and Cd that diffused into the CdMnTe matrix, and diffusion of Te within the matrix.…”
Section: Resultsmentioning
confidence: 99%
“…One method of removing these performance-limiting Te inclusions is post-growth thermal annealing. There are two primary approaches to post-growth thermal annealing [14]: 1) annealing the crystal at a constant temperature (around or above the melting point of Te) in a Cd vapor, and 2) annealing under a temperature gradient to induce the migration of Te inclusions to the hightemperature side of the crystal. In temperature gradient annealing the migration of Te particles leaves regions with fewer and smaller Te inclusions, which can be harvested for detector fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…The start materials are typically high purity cadmium telluride (CdTe) and zinc telluride (ZnTe) [17]. Typical data on Cd 1-x Zn x Te, with x = 0.1, grown by Bridgman technique in our research group at Brookhaven National Laboratory is reported in [4] [17]. The CdTe and ZnTe start materials were commercially obtained with data on their composition.…”
Section: Methodsmentioning
confidence: 99%
“…The CdZnTe crystals are grown under tellurium-rich environments to attain high resistivity that is needed for the detector to operate at room temperature [4]. The major requirements need for detectors to operate at room temperature include high atomic number, large energy band gap, high density, and high electrical resistivity [2] [3].…”
mentioning
confidence: 99%
“…Generally, one annealing method only contains one step. For example, in order to reduce Te inclusions, CdTe-based crystals are generally annealed under a Cd atmosphere [11][12][13].…”
Section: Introductionmentioning
confidence: 99%